The importance of bioequivalence study: focus on clopidogrel (Medical Journal of Indonesia, 2011)
Bioequivalence (BE) study is required to show whether a generic copy product can be interchangeable with the brand innovator product. The aim of this article is to provide the rationale for conducting BE studies, the main products requiring BE studies, the design and conduct of BE studies in general, with focus on clopidogrel. All of the clopidogrel generic products in Indonesia have been shown to be BE to the innovator product Plavix® and they contain API (active pharmaceutical ingredient) clopidogrel form 1 that complies with USP 30, 1997 requirements: the R-enantiomer content is not more than 1%. A proof that bioequivalence (BE) means therapeutic equivalence (TE) is also provided for cardiovascular drugs. Clopidogrel has 2 polymorphic forms, form 1 and form 2, which have the same indications. At least one pivotal study of clopidogrel, CAPRIE, used clopidogrel form 1. An atherothrombotic event may be associated with clopidogrel resistance, which occur in about 4 to 30% of patients treated with conventional doses of clopidogrel. (Med J Indones 2011; 20:149-53)